Olive agroforestry shapes rhizosphere microbiome networks associated with annual crops and impacts the biomass production under low-rainfed conditions - Ben zineb, Ameni; Barkaoui, Karim; Karray, Fatma; Mhiri, Najla; Sayadi, Sami; Mliki, Ahmed; Gargouri, Mahmoud (Frontiers in Microbiology, 2022)
Agroforestry is a promising land-use system to mitigate water deficiency, particularly in semi-arid areas. However, the belowground microbes associated with crops below trees remain seldom addressed. This study aimed at elucidating the effects of olive agroforestry system (AF) intercropped with durum wheat (Dw), barely (Ba), chickpea (Cp), or faba bean (Fb) on crops biomass and their soil-rhizosphere microbial networks as compared to conventional full sun cropping (SC) under rainfed conditions. To test the hypothesis, we compared the prokaryotic and the fungal communities inhabiting the rhizosphere of two cereals and legumes grown either in AF or SC. We determined the most suitable annual crop species in AF under low-rainfed conditions. Moreover, to deepen our understanding of the rhizosphere network dynamics of annual crops under AF and SC systems, we characterized the microbial hubs that are most likely responsible for modifying the microbial community structure and the variability of crop biomass of each species. Herein, we found that cereals produced significantly more above-ground biomass than legumes following in descending order: Ba>Dw>Cp>Fb, suggesting that crop species play a significant role in improving soil water use and that cereals are well-suited to rainfed conditions within both types of agrosystems. The type of agrosystem shapes crop microbiomes with the only marginal influence of host selection. However, more relevant was to unveil those crops recruits specific bacterial and fungal taxa from the olive-belowground communities. Of the selected soil physicochemical properties, organic matter was the principal driver in shaping the soil microbial structure in the AF system. The co-occurrence network analyses indicated that the AF system generates higher ecological stability than the SC system under stressful climate conditions. Furthermore, legumes' rhizosphere microbiome possessed a higher resilient capacity than cereals. We also identified different fungal keystones involved in litter decomposition and drought tolerance within AF systems facing the water-scarce condition and promoting crop production within the SC system. Overall, we showed that agroforestry reduces cereal and legume rhizosphere microbial diversity, enhances network complexity, and leads to more stable beneficial microbial communities, especially in severe drought, thus providing more accurate predictions to preserve soil diversity under unfavorable environmental conditions.